Effects of soccer match-play on unilateral jumping and interlimb asymmetry: a repeated-measures design - Bishop, C.; Read, P.; Stern, D.; Turner, A. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were two-fold: (a) determine the effects of repeated soccer match-play on unilateral jump performance and interlimb asymmetries and (b) examine associations between asymmetry and commonly reported external load variables collected during competition. Single-leg countermovement jumps and drop jumps were collected before and immediately after 5 soccer matches in elite academy soccer players. Global positioning system data were also collected during each match as part of the routine match-day procedures. Single-leg countermovement jump height and concentric impulse showed significant reductions after matches (p < 0.01; effect size [ES]: -0.67 to -0.69), but peak force did not (p > 0.05; ES: -0.05 to -0.13). Single-leg drop jump height and reactive strength also showed significant reductions after matches (p < 0.01; ES: -0.39 to -0.58). No meaningful reductions in asymmetry were present at the group level, but individual responses were highly variable. Significant associations between postmatch reactive strength asymmetry and explosive distance (r = 0.29; p < 0.05), relative explosive distance (r = 0.34; p < 0.05), high-speed running (r = 0.35; p < 0.05), and relative high-speed running (r = 0.44; p < 0.01) were observed. These findings show that unilateral jump tests are more appropriate than asymmetry to detect real change after soccer competition, and practitioners should be cautious about using asymmetry to inform decision-making during the temporal recovery period.